Expression, Mutation, and Amplification Status of EGFR and Its Correlation with Five miRNAs in Salivary Gland Tumours. (9th March 2017) - Boštjančič, Emanuela; Hauptman, Nina; Grošelj, Aleš; Glavač, Damjan; Volavšek, Metka
Abstract : Malignant salivary gland tumours are rare histologically and clinically heterogeneous group of tumours, missing prognostic factors and therapeutic targets. MicroRNAs (miRNAs), small noncoding RNAs, and posttranscriptional regulators of mRNA are poorly described in different subtypes of salivary gland tumours. Epidermal growth factor receptor (EGFR), an important therapeutic target and target of certain miRNAs (i.e., miR-133b ), shows variable degrees of expression in salivary gland tumours. Our study included 70 parotid gland tumours of different histological subtypes. Expression, mutations, and copy number variations (CNVs) of EGFR were determined using immunohistochemistry, single-stranded conformation polymorphism, quantitative polymerase chain reaction (qPCR), and fluorescence in situ hybridization. Expression of miR-99b, miR-133b, miR-140, miR-140-3p, and let-7a was analysed using qPCR. Expression of EGFR was observed in 37% of tumours with low and 40% of tumours with high malignant potential. There were no mutations, with the majority of samples showing polysomy of chromosome 7. Based on histological subtypes, we found differential expression of all five miRNAs. We confirmed association of reactivity of EGFR, miR-133b, miR-140, miR-140-3p, and let-7a with CNV of EGFR and a positive association between miR-133b / let-7a and reactivity of EGFR. Age and need for postoperative radiotherapy were characterized as significant in multivariate survival analysis.